Research and development of an innovative self‐centering energy dissipation brace. (25th June 2018) - Li, Ran; Shu, Ganping; Liu, Zhen; Ge, Hanbin
Summary: Innovative self‐centering energy dissipation braces (SCBs) with super‐elastic shape memory alloy wires are designed and tested on a uniaxial MTS 810 hydraulic servo‐controlled fatigue testing machine. This type of SCB is modeled using finite element method and analyzed by ANSYS software. The test and analysis results show that this type of innovative SCB possesses energy dissipation capacity and self‐centering ability. This paper also describes the multistage working mechanism of the SCBs and exhibits the mechanical behaviors of the braces. The hysteretic behavior of steel frame structures with conventional braces, the buckling‐restrained braces, and the SCBs are compared by conducting low‐frequency cyclic loading. Nonlinear dynamic analyses of steel frame structures with the conventional braces, the buckling‐restrained braces, and the SCBs under frequently occurred earthquake, design basis earthquake, and rare earthquake, respectively, are also performed to compare the seismic responses of steel structures with different braces. The seismic behaviors of these frames are investigated by comparing the peak acceleration, the maximum interstory displacement angle, and the maximum base shear. The results show that the innovative SCB possesses excellent energy dissipation capacity as well as self‐centering ability. Additionally, the innovative SCBs can effectively control the seismic response of the steel frame structure.